2006
DOI: 10.1002/cne.20941
|View full text |Cite
|
Sign up to set email alerts
|

Time frame of mitral cell development in the mice olfactory bulb

Abstract: Along with tufted cells, mitral cells are the principal projection neurons in the olfactory bulb (OB). During the development of the OB, mitral cells migrate from the ventricular zone to the intermediate zone, where they begin to send axons along the lateral olfactory tract (LOT) to the cortical olfactory zones. Subsequently, they lose their tangential orientation, enabling them to make contact with the axons of the olfactory sensory neurons (OSN) that innervate the whole OB. Here, we investigated the distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(171 citation statements)
references
References 54 publications
6
162
0
3
Order By: Relevance
“…During olfactory development, axons from early-born OSNs begin to penetrate the OB around embryonic day (E)14; these axons contact with projection neurons, mitral/tufted cells, at around E16 (10). We have previously found that a large number of OSNs with activated caspases were dispersed throughout the OE in late embryonic stage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During olfactory development, axons from early-born OSNs begin to penetrate the OB around embryonic day (E)14; these axons contact with projection neurons, mitral/tufted cells, at around E16 (10). We have previously found that a large number of OSNs with activated caspases were dispersed throughout the OE in late embryonic stage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glomeruli are designed as contact zone between growth cones of the primary olfactory neurons and dendrites of secondary olfactory neurons, known as mitral and tufted cells located in the olfactory bulb [35]. Primary olfactory neurons, mitral and tufted cells are neurons supporting early synaptic relays of the mouse olfactory system and so arise in a relatively parallel fashion between E9.5 and E10.5 [38]. In our study, we showed for the first time that the olfactory nerve expressed ephrinA5 in early embryogenesis (E12.5), suggesting either an involvement of this molecule in the guidance of primary olfactory neurons into the olfactory bulb or, an implication of ephrinA5 in the fasciculation of primary olfactory axons inside the olfactory nerve, possibly through an interaction with EphA4- and/or EphA5-receptors, shown to be expressed during embryogenesis in the olfactory nerve [35].…”
Section: Discussionmentioning
confidence: 99%
“…These cells form a heterogeneous population expressing a different variety of markers as they migrate towards the CNS (see below). During these early stages, and despite the absence of a fully anatomically differentiated OB, projection neurons have already undergone generation and differentiation processes [49][50][51][52]. The close developmental timing between OE and OB raises the question whether the early OE axons play an inductive role in the OB protrusion and projection neurons' generation [53,54].…”
Section: Main Olfactory System Overviewmentioning
confidence: 99%